The combined effect of socioeconomic status and metabolic syndrome on depression: the Korean National Health and Nutrition Examination Survey (KNHANES) - B. Kim; E. Y. Park (BMC, 2020)
Abstract Background Depression shows different patterns depending on socioeconomic status (SES) and metabolic syndrome (MS). However, the nature of this association remains poorly understood. The aim of this study was to examine whether the combination of MS and lower SES was associated with the prevalence of depression, based on data from the Korea National Health and Nutrition Examination Survey (KNHANES). Methods Data were obtained from a cross-sectional study of 24,102 adults (> 19 years of age) who participated in the KNHANES during 2008-2013 and for whom MS and depression data were available. MS was defined using the diagnostic criteria of the modified National Cholesterol Education Program Adult Treatment Panel III. Measure of depression was ascertained from self-reports of physician diagnosis. Multiple logistic regression analysis was used to evaluate the association between depression and MS as well as SES (alone and in combination). Results Overall, 622 of the 24,102 subjects (2.6%) met the criteria for depression. The prevalence of depression was associated with MS, a lower high-density lipoprotein cholesterol level, an elevated triglyceride level, a lower education level, and a lower household income. Participants with MS and a low SES had a higher likelihood of depression than those without MS and a high SES (odds ratio [OR] = 4.180 for low education level and OR = 3.994 for low household income level). Conclusions This study suggests that the combination of SES and MS may play an important role in depression, which has implications for healthcare policy and depression management.